Exploring Freewriting Technique: a survey of students’ perception at English Department of State University of Sultan Syarif Kasim Riau - Nurhaliza, Yusmalia; Amelia, Rizki (Indonesian Journal of Integrated English Language Teaching, 2023)
AbstractThe purpose of this study was to find out students’ perception on the use of freewriting technique in writing at English Education Department UIN SUSKA Riau. This study was quantitative research with survey approach by giving out questionnaires. Population of the study was the fourth semester of English department students at UIN Suska Riau, the total students of the fourth semester was 110 students. The sample of this research was 26 students selected through purposive sampling. The instrument used in this research was questionnaire. The researcher gave 14 items of statement which was from three indicators (acceptance, understanding, and evaluation). Based on the result of the research, it was found that the students’ perception on the freewriting was at positive category by the percentage 81%. In conclusion of the study, the students have positive perceptions toward freewriting technique. Keywords: freewriting, perceptions, writing technique.